Comparing cost-effectiveness of implant and IUD contraception in women: a systematic review - Amalia, Silviatul; Nafisah, Khilda Durrotun; Muliyani, Navantri; Jusrawati; Dary, Sry Wulan; Sulistyaningsih; Hafidz, Firdaus (BKM Public Health and Community Medicine, 2023)
Purpose: The use of long-acting reversible contraception (LARC) methods, implants, and IUDs, are assessed for cost-effectiveness, which compares cost-effectiveness in technology, environment, and health. The aim is to critically evaluate the economic evaluation of IUDs and implants based on previous scientific evidence, with a review to discuss cost-effectiveness. Methods: The literature review used was a systematic review, and PRISMA-SR 2020 was chosen as a reference for preparing the literature study. The authors used three databases, PubMed, Science Direct, and Wiley, to find scientific evidence of the cost-effectiveness of IUDs and implants. Results: The search in Pubmed (n=119), ScienceDirect (n=1,228), and Wiley (n=83) databases included (n=1,510) articles. Eighty-two articles were assessed for eligibility, and only seven were eligible according to the inclusion criteria for further review. Conclusion: IUDs and implants are two highly effective long-term contraceptive methods for preventing pregnancy, so using IUDs is more cost-effective than implant contraception based on scientific articles that meet the inclusion criteria.